تغریدات الأرشیفات الوطنیة والمکتبات والمتاحف عبر تویتر على شبکة الانترنت :دراسة تحلیلیة - د.عبد الحمید ندا (المجلة الدولية لعلوم المكتبات والمعلومات)
This study discusses national archives and libraries of the USpresidential and museums Tweets across the Twitter online analyticalstudy and what can these tweets providing services for the NationalArchives and beneficiaries at the same time, and aims to study thenational archives that have the Tweets via their own content of Twitter andthe extent of interest in them and adopt standards have on Twitter.The study sample included Tweets National Archives: EgyptianNational Archives –Oman National archives - Saudi Arabia documents,archives national center and - King Abdulaziz DARAH and the NationalArchives of the United Arab Emirates is currently, the National Centre forDocumentation and Research earlier - the US National Archives - USpresidential museums and libraries - British National archivesAmong the most important results of study is: each national archivehave Tweets on Twitter, including a formal documented and most of themare not documented with the exception of the US National Archives have ageneral Tweets and other specialized sub-multiple, and empty most of theNational Archives Tweets of specific criteria and a clear policy with theexception of the US National Archives has a strategy and policy is clearand published, and that Twitter brings the number of photos and videostogether does not specify exactly how many photos in the account and thenumber of videos and in some cases does not mention the number andsophistication in the number of tweets and Followers and Likes andFavorites - moment after moment and hour after hour and day after day - Itis an indicator of the evolution of the expense of the National archives onTwitter